Percepção de pessoas LGBTQIA+ sobre o atendimento em um serviço de atenção às vítimas de violação de direitos humanos - Conceição, Margareth Nunes Neves (2023)
The escalation of the multiple violations suffered by Lesbians, Gays, Bisexuals, Transsexuals, Queer gender (LGBTQIA+) reiterates the exclusion process, which demands measures from the State to face it. Research points out that the impacts of violations imposed on this population, resulting in deaths (physical and social) and mental illness resulting from discrimination. Considering the existence of socially imposed normative standards, based on hetero-cisnormativity as the only possibility of existence, issues such as sexual orientation, gender, race and class are categories that enhance social vulnerabilities, where public policies constitute an important strategy for visibility, social justice and confrontation historical violations of human rights. Thus, the relevance of this study is given by the analysis of the perceptions of LGBTQIA+ people about the service in a service that cares for victims of human rights violations, these impressions will be discussed from the recognition of the function of public policies as a possibility of intelligibility in the context of precariousness more intensely imposed on some lives. OBJECTIVE: Analyze the perceptions of this public about the care provided to them in the context of human rights violations. METHODS: This is a descriptive, exploratory and qualitative study, carried out with people over 18 years of age assisted from 2017 to May 2022, in a care service for LGBTQIA+ people who are victims of rights violations. human, called program Vitória Acolhe carried out by the Center for Specialization in Human Rights, of the Municipal Secretary of Citizenship and Human Rights and Labor, at the Municipality of Vitória _ E.S. A trial sampling strategy was adopted, in which LGBTQIA+ people, according to the inclusion and exclusion criteria, to concentrate a representative population in order to analyze the subject under study. Data collection was carried out between March and June 2022, using a semi-structured form containing data on sociodemographic characterization and questions regarding the participants' perception of the service offered. The collected data were transcribed and, later, with the aid of a software program, Atlas.ti, version 9.0, obtaining categories circumscribed in codes and later grouped according to the identification and possible cores of meaning related to the pursued objectives. The transcripts underwent an enunciation analysis under the theoretical lens of a precarious life, a grieving life, author Butler. RESULTS: Through the semantic synthesis of the speeches, we inferred the perception of LGBTQIA+ people about the care provided in a service that cares for victims of human rights violations, in the city of Vitória_ES, resulting in the analytical categories: reception, resoluteness, justice, professional care and dissemination of the service, which composes the perception of LGBTQIA+ people and point out that, although the service is considered important for facing violations of rights, it has weaknesses that compromise the ability to offer qualified and resolute care to the demands presented by the public served. CONCLUSION: The multiple and historic violations imposed on the LGBTQIA+ population require prompt intervention through various public policies to confront them, which must offer adequate responses to specific demands, in a way that contributes to visibility, respect and guarantee of the right to life. Although there have been advances resulting from the political positioning of social movements towards the State, the insertion of LGBTQIA+ guidelines for access to civil rights guaranteeing basic Human Rights is still recent and recognized as an expansion of fundamental rights, historically centered in the field of health. Even so, what we are witnessing is the escalation of violations driven by the imposition of heteronormativity, producing diverse expressions of LGBTphobia; while public policies to guarantee rights and confront violence are inconsistent or even non-existent, unable to offer effective responses to LGBTQIA+ demands. The dismantling of public policies at the national level is the same that affects the Vitória Acolhe program, evidenced by the perceptions of the people assisted, who point out weaknesses that compromise the effective confrontation of the complex violations of human rights.